2019
DOI: 10.1177/1535370219861283
|View full text |Cite
|
Sign up to set email alerts
|

LCZ696, an angiotensin receptor-neprilysin inhibitor, ameliorates diabetic cardiomyopathy by inhibiting inflammation, oxidative stress and apoptosis

Abstract: Diabetic cardiomyopathy, which refers to the destruction of the structure and function of the heart, is the primary cause of heart failure due to diabetes. LCZ696 is the first angiotensin receptor-neprilysin inhibitor (ARNi) to be used clinically. Our study investigated the role played by LCZ696 during diabetic cardiomyopathy and explored the potential mechanisms underlying these effects. Diabetes was induced by injecting streptozotocin intraperitoneally into mice, and the mice were then divided randomly into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 24 publications
9
44
0
Order By: Relevance
“…In our experiments, the observed increase in proinflammatory factor expression levels in both the blood and heart tissues of TAC mice and the accumulation of macrophages demonstrated that the inflammatory response is active in the TAC model. However, treatment with LCZ696 was able to significantly inhibit the inflammatory response induced by TAC, which is consistent with our previous findings in a model of diabetic cardiomyopathy [18].…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments, the observed increase in proinflammatory factor expression levels in both the blood and heart tissues of TAC mice and the accumulation of macrophages demonstrated that the inflammatory response is active in the TAC model. However, treatment with LCZ696 was able to significantly inhibit the inflammatory response induced by TAC, which is consistent with our previous findings in a model of diabetic cardiomyopathy [18].…”
Section: Discussionsupporting
confidence: 92%
“…The results suggested that decreasing the phosphorylation of Smad2/3 may the mechanism by which SAC/VAL exerts its role in antagonizing Ang -induced brosis. In addition to the above canonical pathways, previous studies have demonstrated that SAC/VAL could inhibit the phosphorylation of JNK and p38MAPK in experimental models of diabetic cardiomyopathy [38]. Our study also found the pronouncedly high level of p-JNK, p-p38MAPK, and p-ERK1/2 in the Ang induced AF model.…”
Section: Discussionsupporting
confidence: 82%
“…The dual effect of LCZ696 causes blood vessel dilation and reduction of the expansion of extracellular fluid volume, which improves heart function in HFrEF patients [ 9 ]. LCZ696 has been shown to possess anti-inflammation and anti-oxidative stress effects in cardiovascular disease models in vivo and in vitro [ 10 , 11 ]. In endothelial cells, AT1-Receptor inhibition possesses a beneficial effect on improving endothelial function [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%